Chemical Composition of the Essential oil, Antibacterial and Antioxidant Activities, Total Phenolic and Flavonoid Evaluation of Various Extracts from Leaves and Fruit Peels of Citrus limon - Bagher Pashazanousi, Mohammad; Raeesi, Mahdi; Shirali, Saeed (Asian Journal of Chemistry, 2012)
The essential oils obtained from the dried leaves, flowers, fruit peels of Citrus limon. were analyzed using GC and GC/MS. Thirty six compounds were identified in the oil of leaves with b-pinene (20.6 %), limonene (16.8 %), neryl formate (14.8 %) and geraniol (9.3 %) as main components. Twnety six compounds were identified in the oil of fruit peels with limonene (60.2 %), b-pinene (12.1 %) and g-terpinene (11.8 %) as main components. Also, evaluating of in vitro antibacterial and antioxidant properties of the methanol and chloroform extracts from the leave of Citrus limon, were performed. The antibacterial test results showed that the chloroformic extracts of the leave medially inhibited the growth of the microorganisms studied especially the Gram-negative strains. The antioxidant potential of the samples was evaluated using DPPH method, inhibition of free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH), the sub-fractions of the chloroform extract were able to reduce the stable free radical DPPH with an IC50 of 29.197. The highest total phenolic content was observed (0.155 mg gallic acid equivalents (GAE)/g fresh matter (FM) for methanolic extract. The highest total flavonoid content was observed in methanolic extract (2.77 mg quercetin equivalents (QE)/g FM).